Técnica spot síntesis y spot ELISA como herramienta para la obtención de bibliotecas de péptidos de interés farmacológico (2019)
The use of peptides as potential molecules for clinical treatments, attracts the attention of pharmaceutical companies interested in expanding their market, making use of low-cost and high-performance technological tools. Therefore, it is of interest in this work to show the benefits offered by the spot synthesis technique in obtaining peptide libraries and suggest this as an easy-to-implement technique, which allows predicting the viability of the peptide in the process of interest. The results obtained made it possible to obtain a peptide library and the Spot ELISA technique was suggested as a method of recognition of the sequences according to the presence of critical amino acids in the peptide structure, key to their activity in pharmacological processes.